Development of high‐performance multicrystalline silicon for photovoltaic industry. (26th October 2013) - Yang, Y. M.; Yu, A.; Hsu, B.; Hsu, W. C.; Yang, A.; Lan, C. W.
Abstract The low cost and high quality of multicrystalline silicon (mc‐Si) based on directional solidification has become the main stream in photovoltaic (PV) industry. The mc‐Si quality affects directly the conversion efficiency of solar cells, and thus, it is crucial to the cost of PV electricity. With the breakthrough of crystal growth technology, the so‐called high‐performance mc‐Si has increased about 1% in solar cell efficiency from 16.6% in 2011 to 17.6% in 2012 based on the whole ingot performance. In this paper, we report our development of this high‐performance mc‐Si. The key ideas behind this technology for defect control are discussed. With the high‐performance mc‐Si, we have achieved an average efficiency of near 17.8% and an open‐circuit voltage (Voc) of 633 mV in production. The distribution of cell efficiency was rather narrow, and low‐efficiency cells (<17%) were also very few. The power of the 60‐cell module using the high‐efficiency cells could reach 261 W as well. Copyright © 2013 John Wiley & Sons, Ltd.